Transcriptome and gene co-expression network analysis revealed a putative regulatory mechanism of low nitrogen response in rice seedlings - Adu, Bright G.; Ohmori, Yoshihiro; Nagano, Astushi J.; Fujiwara, Toru (Frontiers in Plant Science, 2025)
In rice, nitrate (NO3−) and ammonium (NH4+) are the main sources of inorganic nitrogen (N) for growth, which also serve as signaling molecules. Depending on the N status, plants modulate their physiological traits such as root system architecture (RSA) and transcriptome makeup, including N uptake and assimilation genes, to adapt to the amount of N available in the growth medium. In this study, time-course hydroponic experiment under low N (0.4 mM NH4+) and sufficient N (1.6 mM NH4+) was performed using low N tolerant introgression lines, KRIL8 and KRIL37, which carry a small region of the wild rice Oryza rufipogon genome in the Oryza sativa L. cv Koshihikari background. RNA-Seq analysis was used to profile changes in gene expression related to N and carbon metabolism which varied significantly and identified the accumulation of transcripts involved in secondary metabolite synthesis at the peak of low N stress. Weighted gene co-expression network analysis (WGCNA) identified several gene modules and their hub genes, including ion transport related modules consisting of genes that negatively regulate N uptake including OsHHO3, OsBT, and OsACTPK1 in all the lines. The repression of these genes under low N could be a basic mechanism to facilitate N acquisition in rice roots. The network analysis also identified cell activity and cell wall modification modules in the introgression lines which could be coordinated by OsLBD3-1, a paralogue of the Crown rootless1 gene for the promotion of root development to enhance N acquisition under low N conditions. The present analysis revealed the involvement of major pathways for low nitrogen tolerance of the selected lines.